ダイ 30 ジ ナンキョク チイキ カンソク タイ ナツ タイ ホウコク 1988-1989 - 竹内, 貞男; タケウチ, サダオ; Takeuchi, Sadao (1990)
P(論文) 第30次南極地域観測隊は, 隊長江尻全機以下54名で編成された。このうち昭和基地の越冬隊は江尻全機越冬隊長以下29名, あすか観測拠点の越冬隊は召田成美越冬副隊長以下8名である。夏隊は, 副隊長竹内貞男以下17名で編成され, 運輸省船舶技術研究所, 日本鋼管(株)からの2名および南極条約に基づく交換科学者として中国から2名, ノルウエーから1名が同行した。1988年11月14日東京港を出港した「しらせ」はオーストラリアのフリマントル港に寄港した後, 12月17日ブライド湾に到着した。あすか観測拠点での越冬用物資およびセールロンダーネ山地での地学, 生物, 雪氷調査用器材約120tを揚陸した後, 越冬隊員8名と夏期調査隊員(交換科学者1名を含め9名)を残し12月26日昭和基地へ向かった。昭和基地には12月29日に到着, 輸送(約820t), 建設作業, 野外調査等を1989年2月23日まで行った。これまでの間に多目的衛星データ受信システムの建設を行い, 2月1日には越冬交代を行った。「しらせ」は第29次観測隊のセールロンダーネ山地における事故の救援に向かい, 救援活動を終えた後, 第30次夏の調査隊員をブライド湾で収容して昭和基地へ戻った。3月4日第29次越冬隊員と第30次夏隊員, 交換科学者を収容した「しらせ」は昭和基地沖を離れ, 海洋観測を実施しながら東航を開始し, オーストラリアのシドニー港に3月21日入港した。観測隊員はここで下船し, 28日空路成田空港に帰着した。 The 30th Japanese Antarctic Research Expedition (JARE) consisted of 54 members, in which twenty-nine of the wintering party at Syowa Station were led by M.EJIRI, eight of the wintering party at Asuka Station by S.MESHIDA and seventeen of the summer party by S.TAKEUCHI. In addition, two Japanese observers, two Chinese scientists and one Norwegian scientist participated. The icebreaker SHIRASE, leaving Tokyo on 14 November 1988 and after calling at Fremantle, Western Australia, arrived at Breidvika on 17 December. With helicopters, unloadings of about 120t of cargo, eight wintering members for Asuka Station and nine members of the summer expedition party for the Sor Rondane Mountains region (geoscience, biology, and glaciology surveys) were completed on 26 December. Then the ship advanced foward Syowa Station and reached it on 29 December. Unloading of about 820t of cargo, and the summer operations including field research works, the relief of observations, several constructions and renewal of the facilities were carried out until 23 February 1989. The multipurpose satellite data receiving system was also completed. On 1 February all the operations and maintenance of Syowa Station were taken over from JARE-29. There happened the accident that three members of the 29th party fell into the crevasse of the Sor Rondane Mountains area on 13 January, and the ship left Syowa ...